Normal Schools in Latin America - Lima-Jardilino, José Rubens; de Lourdes Alvarado, María (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
The present edition of Rhela, aimed at the debate on the diverse perspectives of the Normal School in Latin America, presents a dossier of eight (06) articles on the subject, most of which are oriented to a history of the present time, with the exception of one article that reflects the history of a Normal Institution between the XIX and XX centuries.  The remaining six (6) final articles deal with various aspects of the history of education in the continent. This issue includes reflections from Brazil, Colombia, Spain, Guatemala, Mexico and the Dominican Republic. The editorial staff of the Journal Historia de la Educación Latinoamericana, has given us the opportunity to begin this turn of current studies on the Normales inviting us to coordinate this dossier on the subject, to whom we thank in a different way for the opportunity.  We invite readers to read the corpus of articles that make up this issue of Rhela.